Micropropagation of Indian laurel (Calophyllum inophyllum), a source of anti-HIV compounds - Thengane, Shubhada Ratnakar; Bhosle, S. V.; Deodhar, Swapna R.; Pawar, K. D.; Kulkarni, D. K. (Current Science, 2006)
An efficient protocol for in vitro micropropagtion of Calophyllum inophyllum (Linn.), an evergreen littoral tree, through multiple shoot formation from seed explants was developed. In vitro germination of the seeds was standardized on Woody Plant Medium (WPM) hormone free and/or supplemented with 6-benzylaminopurine (BAP; 2.22 mu M) and on half or full strength MS medium. Multiple shoot formation was achieved on WPM supplemented with BAP (2.22-44.00 mu M) and thidiazuron (TDZ; 0.91-4.54 mu M) from the decapitated seedling explants. The maximum multiple shoots, 20.9 per explant were induced on TDZ (0.91 mu M) after two subcultures. Elongated shoots of size > 4.0 cm were obtained on all media combinations with an average of 2.2-8.7 per explant. Elongation of the stunted shoots induced on BAP and TDZ was done on half strength WPM without any growth hormones. The elongated shoots on half WPM and/or full strength WPM supplemented with indole-3-butyric acid (2.46-24.60 mu M) alone or in combination with BAP (2.22 mu M) resulted in 52% rooting with 1-5 roots per rooted plant. The micropropagated plants were acclimatized successfully with 77% survival rate after five weeks. These plants were planted in the institute campus for ex situ conservation, where 72% plants are showing good growth and development.
Keywords: Calophyllum inophyllum; ex situ conservation; micropropagation; seed